The Mycobacterium tuberculosis PhoPR virulence system regulates expression of the universal second messenger c-di-AMP and impacts vaccine safety and efficacy - Irene Pérez; Elena Campos-Pardos; Caridad Díaz; Santiago Uranga; Fadel Sayes; Francisca Vicente; Nacho Aguiló; Roland Brosch; Carlos Martín; Jesús Gonzalo-Asensio (Elsevier, 2022)
Cyclic (di)nucleotides act as universal second messengers endogenously produced by several pathogens. Specifically, the roles of c-di-AMP in Mycobacterium tuberculosis immunity and virulence have been largely explored, although its contribution to the safety and efficacy of live tuberculosis vaccines is less understood. In this study, we demonstrate that the synthesis of c-di-AMP is negatively regulated by the M. tuberculosis PhoPR virulence system. Accordingly, the live attenuated tuberculosis vaccine candidate M. tuberculosis vaccine (MTBVAC), based on double phoP and fadD26 deletions, produces more than 25- and 45-fold c-di-AMP levels relative to wild-type M. tuberculosis or the current vaccine bacille Calmette-Guérin (BCG), respectively. Secretion of this second messenger was exclusively detected in MTBVAC but not in M. tuberculosis or in BCG. We also demonstrate that c-di-AMP synthesis during in vitro cultivation of M. tuberculosis is a growth-phase- and medium-dependent phenotype. To uncover the role of this metabolite in the vaccine properties of MTBVAC, we constructed and validated knockout and overproducing/oversecreting derivatives by inactivating the disA or cnpB gene, respectively. All MTBVAC derivatives elicited superior interleukin-1β (IL-1β) responses compared with BCG during an in vitro infection of human macrophages. However, both vaccines failed to elicit interferon β (IFNβ) activation in this cellular model. We found that increasing c-di-AMP levels remarkably correlated with a safer profile of tuberculosis vaccines in the immunodeficient mouse model. Finally, we demonstrate that overproduction of c-di-AMP due to cnpB inactivation resulted in lower protection of MTBVAC, while the absence of c-di-AMP in the MTBVAC disA derivative maintains the protective efficacy of this vaccine in mice.